2018
DOI: 10.1039/c8sm01070f
|View full text |Cite
|
Sign up to set email alerts
|

The air entrapment under a drop impacting on a nano-rough surface

Abstract: We study the impact of drops onto a flat surface with a nano-particle-based superhydrophobic coating, focusing on the earliest contact using 200 ns time-resolution. A central air-disc is entrapped when the drop impacts the surface, and when the roughness is appropriately accounted for, the height and radial extent of the air-disc follow the scaling laws established for impacts onto smooth surfaces. The roughness also modifies the first contact of the drop around the central air-disc, producing a thick band of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 44 publications
0
19
0
1
Order By: Relevance
“…Rough membranes allow air entrapment in the membrane voids, which causes high repulsive forces between the membrane and water, thus inducing a higher hydrophobicity. Furthermore, membranes with nonuniform morphology and nondistributed surface roughness are likely to cause an uneven distribution of the contact angles within the same membrane . Detailed information regarding these observations is outlined in the next section.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rough membranes allow air entrapment in the membrane voids, which causes high repulsive forces between the membrane and water, thus inducing a higher hydrophobicity. Furthermore, membranes with nonuniform morphology and nondistributed surface roughness are likely to cause an uneven distribution of the contact angles within the same membrane . Detailed information regarding these observations is outlined in the next section.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, membranes with nonuniform morphology and nondistributed surface roughness are likely to cause an uneven distribution of the contact angles within the same membrane. 42 Detailed information regarding these observations is outlined in the next section.…”
Section: Afm Analysismentioning
confidence: 99%
“…This method has been used in many prior studies with much success. 9,13,[22][23][24] In a few cases, we also employ a transmission interferometry scheme, similar to our previous studies, 9,11,19,25 where the laser is positioned near the nozzle. The light then shines vertically downward, focusing through the drop and reflecting off of a 451 mirror to the camera.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Li, Vakarelski and Thoroddsen 18 found that with a surface roughness of only 2 nm RMS a faint ring of microbubbles was entrapped marking the location of the initial contact. Langley et al 19 found that by increasing the roughness to between 70 and 130 nm RMS a significant band of microbubbles was formed and the radius of the central air disc was decreased in comparison to a smooth surface.…”
Section: Introductionmentioning
confidence: 99%
“…The super-hydrophobic layer on the glass substrate was fabricated via a spin-coating process 28,29 (Glaco mirror coat "zero", Soft99 Co., Japan) with a spin-coating speed at 300 rpm for 30 s and then dried at room temperature for 15 min. After the super-hydrophobic spin-coating process, two kinds of PDMS reagents (Sylgad 184A/B, Dow Corning Corp., USA) was pre-mixed at a mass ratio of 10 : 1, degassed and stamped on the super-hydrophobic layer for the pattern of droplet SETs by using a polymethylmethacrylate (PMMA)-fabricated stamp.…”
Section: Chip Design and Fabricationmentioning
confidence: 99%